High expression and potential synergy of human epididymis protein 4 and Annexin A8 promote progression and predict poor prognosis in epithelial ovarian cancer - Zhu, Liancheng (Am J Transl Res, 2020)
Epithelial ovarian cancer (EOC) is the most common cause of gynecological cancer-related deaths. Aberrant expression of human epididymis protein 4 (HE4) and Annexin A8 (ANXA8) plays crucial roles in some malignancies; however, their functions in EOC remain unclear. In this study, we utilized immunohistochemistry, real-time PCR, western blotting, immunofluorescence labeling, and gene interaction and enrichment pathway analyses to explore the roles of HE4 and ANXA8 in EOC. They were highly expressed in EOC tissues, which significantly correlated with higher tumor burden, advanced FIGO stages, poor differentiation, presence of > 1 cm residual tumor, and tumor recurrence. The expression patterns of HE4 and ANXA8 were similar, and Spearman’s correlation analysis showed that they were positively correlated (r=0.671, P < 0.001). Large sample database analyses also showed significant positive correlation between their mRNA expression (R=0.304, 0.321, and 0.304 in TCGA, CCLE and GTEx, respectively, all P < 0.001). Kaplan-Meier survival analysis demonstrated that advanced FIGO stages, lymph node metastasis, residual tumor size > 1 cm, and high HE4 and ANXA8 expression were significantly associated with poor overall survival (all P < 0.05). Moreover, multivariate Cox analysis showed that advanced FIGO stages and HE4 expression were independent factors for poor survival (P < 0.001, 0.012, respectively). Interaction network analysis of genes associated with ANXA8, expressed in response to HE4, revealed that these genes participated in TP53 expression, autophagy regulation, and the PID FOXO pathway. In conclusion, the potential synergy between HE4 and ANXA8 may exacerbate the disease condition. Thus, targeting HE4 and ANXA8 could be a novel therapeutic strategy for ovarian cancer.